Moodle and Engineering Education: Literature Review - Tamara ALCANTARA-CONCEPCION; Sonia BRICENO-VILORIA; Víctor LOMAS-BARRIE (Communications of International Proceedings, 2021)
This paper analyzes the literature published in the Scopus database about the Learning Platform Moodle and its use in engineering. First, a search of scientific publications was made, finding most of the documents of this topic are conference papers followed by articles; in both cases, it is observable an evident growing throughout the time. Even when Moodle launched was in 2002, the first paper in Scopus appeared two years later. Next, the metadata of Scopus documents was used to build scientific maps based on the correlation of author keywords; first, maps were built using all author keywords to observe the global landscape. Then the engineering education papers were selected from the total of documents. Science maps show Moodle is used for Online and Blended Learning modalities of Education emphasizing higher Education. Also, a growing number of topics and networks was evident in 2021. It can be explained by the emergence of the Covid-19 pandemic and the educational problems teachers had to face. Finally, the review and categorization of documents considering each title and abstract published from 2019 to 2021 showed hybrid models and learning analytic as the main topics developed.